Influence of temperature cycles on bond between glass fiber-reinforced polymer and concrete - Silva, Manuel Américo Gonçalves da (2018)
Reinforced concrete (RC) beams externally strengthened with glass fiber-reinforced polymer (GFRP) strips bonded to the soffi t may see their load-carrying capacity reduced due to environmental conditions—especially due to the deterioration of bond between the adhesively bonded laminates and concrete, causing premature failure. More research has been published on the detachment of the laminate progressing from the anchorage zone than on failure induced by the formation of fl exural or shear-fl exural cracks in the midspan followed by fi ber-reinforced polymer (FRP) separation and failure designated as intermediate crack (IC) debonding. An experimental program to study degradation of the GFRP laminate beam specimens after accelerated temperature cycles, namely: 1) freezing-and-thawing type; and 2) cycles of the same amplitude (40°C [104°F]) and an upper limit approximately 70% of the glass vitreous transition temperature of the resin, Tg, is described. Effects on the bond stress and ultimate capacity are reported. Substantial differences between shear and bending-induced failure and a decrease of bond stresses and engagement of the laminates on the structural response are analyzed.